Use of Fructosyl Peptide Oxidase for HbA1c Assay - Yonehara, Satoshi (J Diabetes Sci Technol, 2015)
ARKRAY, Inc developed the world’s first automatic glycohemoglobin analyzer based on HPLC (1981). After that, ARKRAY developed enzymatic HbA1c assay “CinQ HbA1c” with the spread and diversification of HbA1c measurement (2007). CinQ HbA1c is the kit of Clinical Chemistry Analyzer, which uses fructosyl peptide oxidase (FPOX) for a measurement reaction. This report mainly indicates the developmental background, measurement principle, and future of the enzymatic method HbA1c reagent.